1999
DOI: 10.1034/j.1399-3054.1999.106103.x
|View full text |Cite
|
Sign up to set email alerts
|

Purification and characterization of a safener‐induced glutathione S‐transferase from wheat (Triticum aestivum)

Abstract: The genome of cultivated wheat is hexaploid, and in consequence a large number of glutathione S‐transferase (GSTs, EC 2.5.1.18) isozymes is expected in that organism. Wheat GST subunits were first analyzed by reverse‐phase high performance liquid chromatography (RP‐HPLC). In root and shoot tissues, subunits 4, 8, and 9 were constitutively expressed whereas subunits 2, 3, and 5 were inducible by the herbicide safener naphthalic anhydride (NA). Significant differences were observed, however, between the distribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
40
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 55 publications
4
40
0
Order By: Relevance
“…Upon treatment of grass crops with safeners, GSTs able to conjugate these herbicides are induced predominantly in shoot tissues. This response is associated with a high level of protection against herbicide damage in maize (Irzyk and Fuerst, 1993;Holt et al, 1995;Dixon et al, 1998), wheat Riechers et al, 1997;Pascal and Scalla, 1999;Xu et al, 2002), rice Hatzios, 2002a, 2002b), and sorghum (Dean et al, 1990;Gronwald and Plaisance, 1998).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Upon treatment of grass crops with safeners, GSTs able to conjugate these herbicides are induced predominantly in shoot tissues. This response is associated with a high level of protection against herbicide damage in maize (Irzyk and Fuerst, 1993;Holt et al, 1995;Dixon et al, 1998), wheat Riechers et al, 1997;Pascal and Scalla, 1999;Xu et al, 2002), rice Hatzios, 2002a, 2002b), and sorghum (Dean et al, 1990;Gronwald and Plaisance, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…It is thought that safeners reduce herbicide toxicity in crops by inducing the expression of GSTs capable of conjugating the herbicide to GSH. GST-mediated metabolism of herbicides in maize (Zea mays; Dixon et al, 1997aDixon et al, , 1997b, sorghum (Sorghum bicolor; Gronwald and Plaisance, 1998), wheat (Triticum aestivum; Cummins et al, 1997;Pascal and Scalla, 1999), rice (Oryza sativa; Wu et al, 1999;Hatzios, 2002a, 2002b), and barley (Hordeum vulgare; Scalla and Roulet, 2002) can be selectively increased by treatment with herbicide safeners. The utility of safeners in agriculture depends on them not enhancing herbicide tolerance in target weeds.…”
mentioning
confidence: 99%
“…Marrs (1996) suggested that, in plants, a common effect of heavy metals, pathogen attack and/or wounding would be the generation of reactive oxygen species and that GSTs are induced in response to oxidative stress to protect cellular compounds from damage. Pascal & Scalla (1999) hypothesized that GSTs can function in plants like glutathione peroxidases, which are major mechanisms of antioxidant defense. In a general manner, Vangronsveld et al (1997) suggested that the induction of antioxidative enzymes is an indirect effect of metal toxicity.…”
Section: Materials and Methods Collectionmentioning
confidence: 99%
“…This enhancement is selective, with the specific GST isoenzymes induced depending on the safener used. For example, treatment of wheat with naphthalic anhydride resulted in the induction of the phi class TaGST2-3, which detoxifies the herbicide fluorodifen (Pascal and Scalla, 1999). In contrast, the tau class isoenzymes TaGST1-2, TaGST1-3, and TaGST1-4, which are active in detoxifying fenoxaprop ethyl, were enhanced in response to the safener fenchlorazole ethyl (Cummins et al, 1997).…”
mentioning
confidence: 99%